Subaltern Studies and African Studies - Lee, Christopher J. (History compass, 2005)
In a context of increasing interest by scholars to break down area studies boundaries, this article addresses the influence and methodological potential of Subaltern Studies within the field of African studies. Originating in South Asia, Subaltern Studies has created a much-debated dialogue between the disciplines of history, postcolonial theory, and cultural studies over the past twenty years. This brief article traces the history of this movement, its parallels at present with scholarship on Africa, and the consequent value this school of history might have on future work in Africa.